Social studies for primary schools - Dosekun, Simidele; Bakare, Adisa; Belgore, Ayisha; Harrison, Eniola (Farafina Educational, 2008)
Umschlag: "Primary 1: This book introduces children to families, neighbourhoods and communities in Nigeria and around the world. Children begin to learn about the ways in which social institutions and rules are structured to meet human needs."